Oral History Interview: Teamster's Union in Kern County. Pete Baclig, Pete Maturin, and Louie Uribe interviewed by Susan McColgan - Baclig, Pete; Maturino, Pete; Uribe, Louie; McColgan, Susan
Pete Baclig and Pete Maturino describe how the Teamsters labor union organized farm workers within Kern County in the 1970s. They describe the major differences between the Teamsters' and the United Farm Workers' union, and also how they believe the Teamsters are providing better working conditions, benefits, and higher wages for employees within their union.